Epidemiology Characteristics of COVID-19 Infection Amongst Primary Health Care Workers in Qatar: March-October 2020 - Al-Kuwari, Mohamed Ghaith; AbdulMalik, Mariam Ali; Al-Nuaimi, Asma Ali; Abdulmajeed, Jazeel; Al-Romaihi, Hamad Eid; Semaan, Sandy; Kandy, Mujeeb (Frontiers in Public Health, 2021)
Background: COVID-19 transmission was significant among Healthcare workers worldwide. In March 2020, Qatar started reporting numbers of COVID-19 positive cases amongst workers in Primary Health Care Corporation (PHCC). The study estimates the burden of COVID-19 infection amongst Primary Health Care Workers in Qatar and examines the demographics characteristics associated with the positivity rate. Method: A cross-sectional descriptive study was conducted amongst Primary healthcare workers between March 1st and October 31st, 2020. The study examined the positivity rate of the different types of Primary healthcare workers and, analyzed the demographic characteristics of the infected persons. Results: 1,048 (87.4%)of the infected HCWs belonged to the age group below 45 years, and 488 (40.7%) HCWs were females. 450 (37.5%) were HCWs clinical staff working in one of the 27 PHCC HCs; Despite the increased patient footfall and risk environment, the COVID HCs had an attack rate of 10.1%, which is not significantly different from the average attack rate of 8.9% among staff located in other HCs (p-value =0.26). Storekeepers, engineering & maintenance staff, housekeeping staff, support staff, and security staff (outsourced non-clinical positions) had the highest positivity rates, 100%, 67.2%, 47.1%, 32.4%, and 29.5% respective positivity rates. Conclusion: The elevated risk of infection amongst outsourced non-clinical healthcare workers can be explained by environmental factors such as living conditions. On the other hand, better containment within clinical healthcare workers can be attributed to strict safety training and compliance with preventative measures which is recommended to be implemented across all settings.